Do Village Organizations Make a Difference in African Rural Development? A Study for Senegal and Burkina Faso - Bernard, Tanguy (2012)
Quantitative and qualitative analyses are used to assess the existence of village organizations (VOs), their performance, and members' participation in benefits in Senegal and Burkina Faso. VOs are classified into market-oriented (MOs) and community-oriented (COs). Results show that organizations are present in a majority of villages and include a high share of rural households. Diffusion of MOs is limited by isolation and social conservatism. Performance is constrained by low professional management capacity and lack of access to resources. With elaborate administrative rules in place, participation in benefits shows no occurrence of leader or elite capture in MOs.